The antimicrobial effect of R-limonene and its nano emulsion on Enterococcus faecalis - In vitro study - İlke Doğa Şeker; Tayfun Alaçam; Gülçin Akça; Aysel Yılmaz; Sevgi Takka (European Oral Research)
Purpose: This study aimed to evaluate the effectiveness of R-limonene and its nano emulsion formulation against Enterococcus faecalis (E. faecalis) in infected root canals.Materials and Methods: A nano emulsion containing 20% R-limonene was prepared using the phase inversion method. E. faecalis was cultivated, and MIC/MBC values were determined through the macrodilution method. Standardized E. faecalis suspensions were used to infect the root canals ex vivo. Subsequently, R-limonene, nano emulsion containing 20% R-limonene, calcium hydroxide, and sterile saline were applied to the infected root canals for 7 days at the determined MIC/MBC dose. The root canals were sampled, and droplets were plated onto Mueller-Hinton agar plates, and viable bacteria (Colony Forming Units, CFU/mL) were counted. Statistical analyzes were performed based on the data.Results: Statistically similar efficacy was observed between test materials on the root canal samples. All test materials were significantly more effective than the saline control (p<0.05), however, none of the test materials completely eliminated E. faecalis from root canals.Conclusion: Although the effects of R-limonene on E. faecalis in infected root canals appeared to be like calcium hydroxide, with its broad antibacterial spectrum, gutta-percha softening and cleansing benefits, it was considered that it could considered among antimicrobials that could be used especially in endodontic retreatments alone or in synergistic combinations.